Sobre o Projeto do Nível de Entrelaçamento para Transmissão de Códigos de Bloco em Canais com Memória DOI: 10.14209/jcis.2002.3 - Ramos, Rodrigo; Pimentel, Cecilio (Journal of Communication and Information Systems, 2015)
This paper presents an enumerative method to evaluate analytically the performance of block codes on channels with memory. The effect of interleaving with finite interleaving depth is explicitly studied. We identify the conditiuns under which the interleaving is beneficial or harmful to the system. In applications with severe delay constraint, it is demonstrated that the interleaver works better for a code with smaller block length. These analysis allow us to evaluate the tradeoff between the code rate and the interleaving depth to obtain a certain performance.